From recommendations to practice: eight years of challenges for children's health in primary care services in the interior of Sao Paulo State, Brazil - Sanine, Patricia Rodrigues [UNESP]; Tortorelli Zarili, Thais Fernanda [UNESP]; Nunes, Luceime Olivia [UNESP]; Dias, Adriano [UNESP]; Lodeiro Castanheira, Elen Rose [UNESP] (Cadernos Saude Publica, 2018)
This article aims to identify changes in indicators for the organization of children's health services in primary care in the State of Sao Paulo, Brazil. An evaluative study was conducted with three series of cross-sectional evaluations with participation by 81 services, involving 32 municipalities (counties) in the central-west region of the state, who answered the Quali AB questionnaire in 2007, 2010, and 2014. The analysis used 74 children's health indicators and 7 services indicators. Comparison of the indicators evidenced changes in the organization of children's healthcare, with an improvement in the majority of the indicators in 2010 and maintenance or worsening in 2014, compared to 2007. In conclusion, children's health policy recommendations have not been fully realized in the organization of the supply of comprehensive care, although relevant issues such as childhood obesity and violence have been addressed by a few services.
Keywords: Child Health; Primary Health Care; Health Evaluation; Health Services; Organization and Administration